2020
DOI: 10.1101/2020.02.07.20021071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incorporating Human Movement Data to Improve Epidemiological Estimates for 2019-nCoV

Abstract: Estimating the key epidemiological features of the novel coronavirus (2019-nCoV) epidemic proves to be challenging, given incompleteness and delays in early data reporting, in particular, the severe under-reporting bias in the epicenter, Wuhan, Hubei Province, China. As a result, the current literature reports widely varying estimates. We developed an alternative geostratified debiasing estimation framework by incorporating human mobility with case reporting data in three stratified zones, i.e., Wuhan, Hubei P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 12 publications
1
40
1
1
Order By: Relevance
“…Technically, the available population migration data [7] covers the period from Jan 01 to Jan 22, so the timing of Wuhan lockdown investigated in this study is confined within this period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Technically, the available population migration data [7] covers the period from Jan 01 to Jan 22, so the timing of Wuhan lockdown investigated in this study is confined within this period.…”
Section: Discussionmentioning
confidence: 99%
“…Wuhan has a population of around 15.39 million, including a resident population of 9 million, and nearly 6.39 million floating population exported before Jan 23 [7]. The population exported from Wuhan is the main source of imported cases in the rest of China.…”
Section: Data Source and Framework Of The Estimation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…R 0 is an epidemiologic matrix used to describe the transmissibility of infectious agent. Various studies [22,28,[46][47][48][49][50] indicated the number of expected cases directly generated by a single infected case is within the range of 0.8-5.7. As the aforementioned studies approximated the virus incubation period at 5.2-12.5 days, the expected epidemic doubling time of COVID-19 could be in the range of 2.9-8.4 days.…”
Section: Transmission Modelmentioning
confidence: 99%
“…Most of the above-mentioned studies simulated the Wuhan epidemic dynamic network by utilizing a deterministic susceptible-exposed-infected-recovered (SEIR) model that categorizes the population into four states: susceptible individuals (S), asymptomatic individuals during the incubation period (E), confirmed infectious individuals (I), and recovered individuals (R). A SEIRDC model enhanced from the standard SEIR model by introducing dead and auxiliary variable (DC) [50] is also used for COVID-19 investigation. A geological-stratified debiasing approach is incorporated into the SEIRDC model to include the latent infection ratio (L&I) amongst the people traveling from Wuhan to other destinations in mainland China to improve the overall epidemiological estimation of the coronavirus.…”
Section: Transmission Modelmentioning
confidence: 99%